2017
DOI: 10.1136/bcr-2017-220891
|View full text |Cite
|
Sign up to set email alerts
|

Acute myeloid leukaemia masquerading as a primary CNS tumour

Abstract: In children with newly diagnosed acute myeloid leukaemia (AML), myeloid sarcomas (MS) of the central nervous system (CNS) are rare. Since MS involving the CNS are potentially curable, timely recognition is paramount. Establishing a diagnosis may be problematic as they can easily mimic primary CNS neoplasms. We report the case of a 5-year-old boy with AML with t(8;21)(q22;q22) rearrangement who presented with a massive intracranial MS and rapid clinical deterioration suggestive of a meningioma or a primitive ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The atypical features of the mass (extra-axial location; extensive infiltration into adjacent structures, including bony and soft tissues),2 and the finding of myeloblasts in the peripheral blood led to the diagnosis of AML with CNS-MS, thereby avoiding a potentially morbid surgical procedure and subsequent delay in definitive therapy. A similar presentation of CNS-MS was described in a young child with an intracranial midline falxian mass and peripheral blood myeloblasts 3. Despite this atypical presentation of AML, patients with CNS-MS have been shown to have superior outcomes compared with patients with non-CNS-MS or absence of MS 1…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…The atypical features of the mass (extra-axial location; extensive infiltration into adjacent structures, including bony and soft tissues),2 and the finding of myeloblasts in the peripheral blood led to the diagnosis of AML with CNS-MS, thereby avoiding a potentially morbid surgical procedure and subsequent delay in definitive therapy. A similar presentation of CNS-MS was described in a young child with an intracranial midline falxian mass and peripheral blood myeloblasts 3. Despite this atypical presentation of AML, patients with CNS-MS have been shown to have superior outcomes compared with patients with non-CNS-MS or absence of MS 1…”
Section: Discussionmentioning
confidence: 66%
“…MS presenting as an isolated intracranial mass in AML is rare in children, 1 but may occur at the time of initial diagnosis, 2,3 or as a new finding at relapse. 4,5 In the present case, the intracranial findings preceded the diagnosis of AML.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutated nucleophosmin 1 (NPM1) is the most frequent mutation reported in MS [11] . MS is commonly associated with the translocation t(8;21)(q22; q22) [11,17] . MS is a rare neoplasm, so our knowledge is limited and mostly based on previous case reports and retrospective studies.…”
Section: Discussionmentioning
confidence: 99%
“…8 In the brain, MS frequently involves the parenchyma (43-54%), followed by dura (41%). 2,8 Though deemed rare, several large treatment trials and case series have been published in the literature reporting CNS-MS. [9][10][11][12][13][14][15][16][17] In the Children's Cancer Group (CCG) protocols for intensive-timing chemotherapy treatment for AML, 10 the authors reported that of the 1459 patients, 19 (1%) had CNS-MS, while the NOPHO (Nordic Society of Pediatric Hematology and Oncology)-AML 2004 trial of 315 patients found 22 (7%) had CNS disease but only 2 had MS in the dural/epidural space. 9 The pathogenesis of CNS infiltration is unclear; it is hypothesized that leukemic cell infiltrates are capable of migration from the bone marrow of the periosteum to the dura, into the underlying brain parenchyma once there is disruption of the pial-glial barrier.…”
Section: Topic Review: Dr Gharementioning
confidence: 99%